2013
DOI: 10.1097/psy.0b013e318286be43
|View full text |Cite
|
Sign up to set email alerts
|

Specific Biases for Identifying Facial Expression of Emotion in Children and Adolescents With Conversion Disorders

Abstract: The observation of faster reaction times to sad faces in children and adolescents with conversion disorders suggests increased vigilance and motor readiness to emotional signals that are potential threats to self or to close others. These effects may occur before conscious processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 58 publications
(51 reference statements)
5
34
0
Order By: Relevance
“…Reduced accuracy for recognising emotional facial expressions and reduced phasic skin conductance responses (SCRs) was observed in FND-seiz participants in one study 15. Altered reaction times for explicit identification of sad and happy faces have also been reported in children and adolescents with FND,32 alongside elevated heart rate (HR) and reduced heart rate variability (HRV) in the same sample 33. Additionally, avoidant behavioural responses to angry faces have been observed in FND-seiz 34.…”
Section: Emotional Processing In Fnd: a Narrative Reviewmentioning
confidence: 93%
“…Reduced accuracy for recognising emotional facial expressions and reduced phasic skin conductance responses (SCRs) was observed in FND-seiz participants in one study 15. Altered reaction times for explicit identification of sad and happy faces have also been reported in children and adolescents with FND,32 alongside elevated heart rate (HR) and reduced heart rate variability (HRV) in the same sample 33. Additionally, avoidant behavioural responses to angry faces have been observed in FND-seiz 34.…”
Section: Emotional Processing In Fnd: a Narrative Reviewmentioning
confidence: 93%
“…First, in a study using a facial emotion-identification task, patients from the current cohort demonstrated faster reaction times than controls, (Kozlowska et al, 2013a) suggesting increased motor readiness with concomitant activation of the motor and sympathetic systems. Second, in a study assessing integrative capacity within narratives (Kozlowska et al, 2011) and in a study assessing cognitive function, (Kozlowska et al, 2015a) patients demonstrated difficulties in integrating autobiographical information and also decreased performance on cognitive tasks dependent on prefrontal cortex (PFC) function.…”
Section: Introductionmentioning
confidence: 90%
“…Fifty-seven children and adolescents with functional neurological symptom disorder (41 girls; 16 boys) aged 8.5–18 years were recruited between August 16, 2006, and August 16, 2010, from a paediatric tertiary-care hospital in New South Wales, Australia, and took part in a series of studies (Kozlowska et al, 2013a, Kozlowska et al, 2011, Kozlowska et al, 2015a, Kozlowska and Williams, 2010). Because data for the auditory oddball were missing for seven patients, seven other patients matched for age and sex—recruited during August 17, 2010, to April 31, 2014—replaced the 7 patients for whom there was no data, yielding 41 girls and 16 boys aged 8.43–18 years (mean: 13.46 years, SD: 2.14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there has recently been a study of children with CD which found shorter reaction times to negative emotional faces compared to neutral faces consistent with a state of increased vigilance and motor readiness to emotional stimuli [10]. Further evidence of an abnormal state of emotional arousal in CD also comes from findings of elevated basal cortisol levels in the seizure variant of CD [11] that correlate with attentional bias towards threatening stimuli [12].…”
Section: Introductionmentioning
confidence: 93%